TMEM187-IRAK1 Polymorphisms Associated with Rheumatoid Arthritis Susceptibility in Tunisian and French Female Populations: Influence of Geographic Origin - Olfa Khalifa; Nathalie Balandraud; Nathalie Lambert; Isabelle Auger; Jean Roudier; Audrey Sénéchal; David Geneviève; Christophe Picard; Gérard Lefranc; Isabelle Touitou; Bakridine M’Madi Mrenda; Cécilia Benedito; et al. (Journal of Immunology Research)
Polymorphisms have been identified in the Xq28 locus as risk loci for rheumatoid arthritis (RA). Here, we investigated the association between three polymorphisms in the Xq28 region containing TMEM187 and IRAK1 (rs13397, rs1059703, and rs1059702) in two unstudied populations: Tunisian and French. The rs13397 G and rs1059703 T major alleles were significantly increased in RA patients (n=408) compared with age-matched controls (n=471) in both Tunisian and French women. These results were confirmed by a meta-analysis replication study including two independent Greek and Korean cohorts. The rs1059702 C major allele was significantly associated with RA, only with French women. In the French population, the GTC haplotype displayed a protective effect against RA, while the ATC, GCC, and GTT haplotypes conferred significant risk for RA. No association for these haplotypes was found in the Tunisian population. Our results replicated for the first time the association of the three Xq28 polymorphisms with RA risk in Tunisian and French populations and suggested that RA susceptibility is associated with TMEM187-IRAK1 polymorphisms in women. Our data further support the involvement of X chromosome in RA susceptibility and evidence ethnicities differences that might be explained by differences in the frequencies of SE HLA-DRB1 alleles between both populations.